A concessão da assistência jurídica gratuita e integral à pessoa jurídica de direito privado enquanto mecanismo de cidadania - Moreira, Eliane Trevisani (2009)
Motivation for this research started with our indignation of the treatment given to legal entities with private rights, specially ones with financial interests which we understand as being without reason and discriminatory. Firstly, we are searching to study the principals and constitutional guarantees, following we explain concepts and interpretation in general lines of legislative texts of the Brazilian juridical ordainment jointly with the exam of reiterated monochromic decisions and collegiate, the analysis of this and its implications and reflection over a persons dignity. We concluded, demonstrating the affront perpetrated against the constitutional guarantee of access to justice, the right of action and its fundamental principles of the Right of Democratic State